Engineering Education Transformation: Project-Based Learning’s Effect on Problem-Solving and Lifelong Learning - M., Madhavi; T., Neetha; Indrakanti, Raghu (Journal of Engineering Education Transformations, 2025)
This paper examines the traditional model of classroom instruction method has its limitations in engaging students and fostering deep understanding. In response, educators have increasingly turned to flipped classroom pedagogy, a method that reverses the traditional order of instruction by delivering content outside of class and utilizing class time in class activities. This research paper investigates the efficacy of flipped classrooms pedagogy in enhancing student participation and improving learning outcomes. A ensemble approach was implemented, using quantitative analysis of student performance data with qualitative assessments of student experiences and perceptions. The findings reveal promising benefits of flipped classroom implementation, including increased student engagement, improved understanding of course material, and enhanced critical thinking skills. However, challenges such as technological barriers and student resistance to independent learning were also identified. The discussion highlights the implications of these findings for educators and proposes new approaches for future study and practice.